Examining the Moderating Role of Ease of doing Business with Foreign Restrictions on Foreign Direct Investment - Naushahi, Muhammad Mudassar; Rehman, Hafeez ur (Pakistan Journal of Humanities and Social Sciences, 2024)
Foreign direct investment is crucial for the development through the creation of new jobs. Sometimes, the massive flow of foreign investment creates many challenges if it needs to be properly managed. The present study examines the moderating role of Ease of Doing Business (EDB) with aggregated and disaggregated FDI restrictions on FDI inflows. The panel data from 2003 to 2022 is collected from OECD and WDI databases. The empirical results are estimated using the Panel Quantile regression. It shows that all types of restriction propose an inverted U-shaped relationship to determine the FDI inflows in OCED countries. EDB is used as the moderator, shifting the turning point to the left side of the inverted U-shaped curve. In the case of non-OECD countries, most types of restrictions show a U-shaped relationship to determine the FDI inflows. EDB is also used as the moderator in this case, shifting the tuning point to the right side of the U-shaped curve. Both results show that EDB significantly reduces the FDI restrictions and increases FDI inflows. The countries should pay special attention to increasing the ease of business indicators.